Insights of the tubulin code in gametes and embryos: from basic research to potential clinical applications in humans. Issue 3 (21st September 2018) - Amargant, Farners; Barragan, Montserrat; Vassena, Rita; Vernos, Isabelle
Abstract: Microtubules are intracellular filaments that define in space and in time a large number of essential cellular functions such as cell division, morphology and motility, intracellular transport and flagella and cilia assembly. They are therefore essential for spermatozoon and oocyte maturation and function, and for embryo development. The dynamic and functional properties of the microtubules are in large part defined by various classes of interacting proteins including MAPs (microtubule associated proteins), microtubule-dependent motors, and severing and modifying enzymes. Multiple mechanisms regulate these interactions. One of them is defined by the high diversity of the microtubules themselves generated by the combination of different tubulin isotypes and by several tubulin post-translational modifications (PTMs). This generates a so-called tubulin code that finely regulates the specific set of proteins that associates with a given microtubule thereby defining the properties and functions of the network. Here we provide an in depth review of the current knowledge on the tubulin isotypes and PTMs in spermatozoa, oocytes, and preimplantation embryos in various model systems and in the human species. We focus on functional implications of the tubulin code for cytoskeletal function, particularly in the field of human reproduction and development, with special emphasis on gamete quality and infertility. Finally, we discuss some of the knowledge gaps and propose future research directions. Abstract : The tubulin code is emerging as an important regulator of microtubule function that impacts gamete and embryonic development.